2020
DOI: 10.1371/journal.pone.0239887
|View full text |Cite
|
Sign up to set email alerts
|

Routine screening for SARS CoV-2 in unselected pregnant women at delivery

Abstract: Background South America has become the epicenter of coronavirus pandemic. It seems that asymptomatic population may contribute importantly to the spread of the disease. Transmission from asymptomatic pregnant patients' needs to be characterized in larger population cohorts and symptom assessment needs to be standardized. Objective To assess the prevalence of SARS CoV-2 infection in an unselected obstetrical population and to describe their presentation and clinical evolution. Methods A cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 30 publications
5
44
0
6
Order By: Relevance
“…We summarize the evidence in terms of the number of studies and the range, median, and interquartile range (IQR) for persons who tested positive but had no symptoms at the time of PCR testing or who reported having had no symptoms before or at the time of antibody testing. Thirty of the studies included a list of specific symptoms, independent of signs, used to determine symptomatic status ( 10–14 , 17 , 18 , 22–28 , 35 , 36 , 38 , 42 , 49 , 51 , 55–57 , 60–62 , 64 ). Many of the remaining studies used some variation of the catch-all phrase “symptoms compatible with COVID-19.”…”
Section: Resultsmentioning
confidence: 99%
“…We summarize the evidence in terms of the number of studies and the range, median, and interquartile range (IQR) for persons who tested positive but had no symptoms at the time of PCR testing or who reported having had no symptoms before or at the time of antibody testing. Thirty of the studies included a list of specific symptoms, independent of signs, used to determine symptomatic status ( 10–14 , 17 , 18 , 22–28 , 35 , 36 , 38 , 42 , 49 , 51 , 55–57 , 60–62 , 64 ). Many of the remaining studies used some variation of the catch-all phrase “symptoms compatible with COVID-19.”…”
Section: Resultsmentioning
confidence: 99%
“…The maternal and neonatal clinical course of our studied population showed similar maternal and perinatal outcomes when comparing women with and without SARS-CoV-2 infection. Previous studies using only PCR testing during labor and delivery, in both symptomatic and asymptomatic COVID-19 patients, reported high rates of cesarean delivery among these women [ 15 , 16 ]. In a series of 675 pregnant women from New York admitted for labor and delivery, Prabhu et al [ 15 ] reported a slight increase in the rate of cesarean delivery in symptomatic COVID-19 women (46.7%) compared to asymptomatic ones (45.5%).…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 675 pregnant women from New York admitted for labor and delivery, Prabhu et al [ 15 ] reported a slight increase in the rate of cesarean delivery in symptomatic COVID-19 women (46.7%) compared to asymptomatic ones (45.5%). Díaz-Corvillón et al [ 16 ] in Chile described another study for SARS-CoV-2 in 583 patients using only PCR during labor and delivery admission. They reported a 43.2% rate of asymptomatic women and no significant differences in perinatal outcomes, but a trend towards a higher rate of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations